2019
DOI: 10.1175/jamc-d-18-0011.1
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Heavy Precipitation Biases in the TRMM PR and TMI Products Assessed with CloudSat and Reanalysis Data

Abstract: This study aims to characterize the background physical processes in the development of those heavy precipitation clouds that contribute to the Tropical Rainfall Measuring Mission (TRMM) active and passive sensor differences. The combined global observation data from TRMM, CloudSat, and European Centre for Medium-Range Weather Forecasts (ECMWF) interim reanalysis (ERA-Interim) from 2006 to 2014 were utilized to address this issue. Heavy rainfall events were extracted from the top 10% of the rain events from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…In addition, the CAPE and CTH−SH of extreme heavy rain clouds in the Eastern Pacific Ocean are much lower than those in the Western Pacific Ocean. These results are consistent with the relatively suppressed deep convection in the Eastern Pacific in Sekaranom and Masunaga (2019), and can vary with interannual changes of the El Niño Southern Oscillation (Henderson et al 2018). However, the mean CTH−SH of extreme heavy rain clouds in the Eastern Pacific is still higher than that in Korea/Japan because of relatively high CTH in the EP (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, the CAPE and CTH−SH of extreme heavy rain clouds in the Eastern Pacific Ocean are much lower than those in the Western Pacific Ocean. These results are consistent with the relatively suppressed deep convection in the Eastern Pacific in Sekaranom and Masunaga (2019), and can vary with interannual changes of the El Niño Southern Oscillation (Henderson et al 2018). However, the mean CTH−SH of extreme heavy rain clouds in the Eastern Pacific is still higher than that in Korea/Japan because of relatively high CTH in the EP (Fig.…”
Section: Resultssupporting
confidence: 82%
“…The regional differences between heavy rain clouds, revealed in previous studies, can be related to problems with estimating satellite precipitation. For example, Sekaranom and Masunaga (2019) showed that the regional difference of PR and TMI rain products (focusing on oceanic and continental convection) occur because PR tends to detect more organized heavy rain systems under humid environments, whereas TMI rainfall is sensitive to deep convective clouds under relatively dry and unstable conditions. Figure 1a shows the average value of TMPA summer precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, knowledge related to mean inter-product differences are not necessarily applicable to extremes, given that satellite-derived extreme precipitation is often associated with some cloud property (e.g. cloud top height or precipitation water content) rather than the intensity of precipitation itself [9].…”
Section: Introductionmentioning
confidence: 99%
“…5a), whereas in other months it mainly underestimated the precipitation intensity with a mean RE of approximately −10%. The types of major rain clouds in different seasons affect the performance of TRMM-3B42v7 precipitation estimate notably: studies have shown that the organized stratiform rain may cause TRMM Microwave Imager (TMI) to overestimate precipitation, while deep-isolated rain may result in underestimation (Sekaranom and Masunaga 2018). Meanwhile, CMORPH underestimated the monthly precipitation in all 12 months (Fig.…”
Section: Monthly Precipitation Evaluationmentioning
confidence: 99%